Correlation Between RET-He and Quality of Life in Chronic Kidney Disease Patients with Routine Hemodialysis: A Study at Ulin General Hospital Banjarmasin - Fariz, Adlan; Rudiansyah, Mohammad; Kurniaatmaja, Enita Rakhmawati; Wulandari, Nanik Tri; Pratiwi, Dewi Indah Noviana (PERNEFRI (PERHIMPUNAN NEFROLOGI INDONESIA), 2024)
Background: The 2018 Riskesdas report revealed that the incidence of chronic kidney disease (CKD) affects 0.38% of Indonesia’s population. Anemia frequently complicates CKD, especially in patients undergoing regular hemodialysis. Reticulocyte hemoglobin equivalent (RET-He) assesses hemoglobin content in reticulocytes, indicating iron availability for erythropoiesis in the bone marrow. CKD significantly impacts patients' socio-economic status, heightening morbidity and mortality while diminishing quality of life. The relationship between RET-He and the quality of life in CKD patients on routine hemodialysis remains unclear. Objective: To investigate the correlation between RET-He and quality of life in CKD patients undergoing routine hemodialysis. Methods: A cross-sectional observational analytical study with data from medical records of CKD patients receiving routine hemodialysis between October 1st and October 30th, 2021. The Spearman correlation test was used for analysis. Results: This study included 92 patients, consisting of 40 males and 52 females, with a median age of 50 years and RET-He values at 31. Quality of life metrics included physical function (800, range: 0-1000), physical limitations (300, range: 0-400), body pain (175, range: 75-255), general health (475, range: 225-600), vitality (320, range: 200-400), social function (175, range: 75-200), emotional limitations (300, range: 100-300), and mental health (380, range: 160-500). The correlation analysis revealed no significant relationships: physical function (p=0.359), physical limitations (p=0.813), body pain (p=0.373), general health (p=0.547), vitality (p=0.616), social function (p=0.828), emotional limitations (p=0.482), and mental health (p=0.136). Conclusion: There is no significant correlation between RET-He levels and the quality of life in CKD patients undergoing regular hemodialysis.